The clinical Erich Fromm : personal accounts and papers on therapeutic technique - Funk, Rainer (Contemporary psychoanalytic studies ;, 2009)
"Rainer Funk's edited book is immensely valuable because it presents Fromm's clinical ideas and clinical style through the voice of his supervisees, students, colleagues, and friends. Funk's book provides a timely and important addition to our understanding of Fromm. It fills a gap in the secondary literature by demonstrating the way in which Fromm was an especially skillful and talented clinician, in addition to being a writer of great renown. By offering first-hand accounts of their work with Fromm, the contributors help readers to grasp how the "clinical Erich Fromm" worked in his psychoana